Assessing Fish Diversity in the Chishui River Using Environmental DNA (eDNA) Metabarcoding - Jing Gao; Jing Zhang; Chengrong Pan; Sheng Xu; Yajie Wu; Wei Lv; Min Hong; Yuxin Hu; Yingru Wang (Fishes)
Since 2017, a fishing ban in the Chishui River (China) has reduced human disturbances, yet the early-stage recovery of fish resources remains unquantified. Here, we applied environmental DNA (eDNA) metabarcoding to assess fish diversity and restoration status across its upper, middle, and lower reaches. An analysis of operational taxonomic units (OTUs) revealed higher unique than shared OTUs among reaches, indicating significant spatial partitioning of fish communities. The upper reaches exhibited the highest diversity due to reduced human activity, attributed to greater species richness, while the middle and lower reaches showed similar community structures. Key findings include the following: (1) the detection of rare endemic species (Schizothorax) and non-native Oreochromis DNA, suggesting invasion risks; (2) the investigation revealed a predominance of small-bodied fish species, indicating that large-bodied fish populations in the Chishui River (China) remained relatively scarce; (3) the recovery of demersal fish DNA from surface waters, confirming eDNA’s broad detection capacity. The results indicate that the fishing ban has contributed to the partial recovery of the fish community in the Chishui River (China). However, risks of biological invasion (e.g., Oreochromis species) remain, and large-bodied fish are still relatively scarce. To ensure effective conservation, it is critical to strengthen the monitoring and evaluation of the fishing ban’s effectiveness and implement timely measures to prevent invasive species proliferation.